Westward‐Propagating Disturbances Shape Diverse MJO Propagation - Wei, Yuntao; Ren, Hong‐Li; Duan, Wansuo; Sun, Guodong (Geophysical research letters, 2023)
Understanding eastward‐propagating mechanisms of the Madden–Julian Oscillation (MJO) is of great importance for the subseasonal prediction of extreme weather and climate worldwide. Using global satellite observations and reanalysis data, this study unravels that dual combinations of strong/weak westward‐ (ISOw) and eastward‐propagating intraseasonal oscillation (ISOe) can shape diverse MJO propagations documented previously using clustering analysis. The dry ISOw signals from the Central Pacific strengthen the leading suppressed convection over the Western Pacific (WP) and, on the contrary, weaken the moist ISOe convection over the Maritime Continent. Thus, when ISOe is weak over the WP, the strong (weak) dryness of ISOw likely causes a jump‐like (stand‐like) MJO mode. In contrast, a propagating MJO is supported when ISOe becomes strong over the WP, and a further strengthening of the ISOw dryness will presumably accelerate MJO; moreover, a weakening of ISOw might slow down the MJO speed. Plain Language Summary Owing to the eastward propagation of the Madden–Julian Oscillation (MJO), tropical winds and precipitation usually oscillate in a broad life cycle of 20–100 days. The subseasonal (longer than 2 weeks but shorter than one season) prediction of extreme events, such as tropical cyclones, droughts, and heat waves, relies closely on an adequate understanding of the propagation mechanisms of MJO. Recently, clustering analysis has revealed four MJO propagation patterns, including stand, jump, slow, and fast modes. However, the underlying mechanisms of the origin of MJO propagation diversity are still elusive. Herein, we offer a novel explanation from the perspective of atmospheric westward‐propagation disturbances (WPDs). These WPDs, which first appeared over the Central Pacific, can cause stand‐ and jump‐like MJO modes when the eastward‐propagating 20–100‐day dry signals are weak over the Western Pacific. Otherwise, fast and slow MJO modes will be supported when the WPDs are further strengthened and weakened, respectively. These results highlight that the WPDs and their triggering place, that is, the Central Pacific, might serve as key ingredients for better understanding the MJO dynamics and predictability. Key Points Dual combinations of strong/weak westward‐ and eastward‐propagating disturbances shape Madden–Julian Oscillation (MJO) diversity Westward‐propagating disturbances control the formation of stand and jump MJOs and distinguish fast and slow MJOs Eastward‐propagating disturbances primarily help MJO cross the Maritime Continent barrier